The Making of a Nineteenth-Century Profession: Shipmasters and the British Shipping Industry - Burton, Valerie (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1990)
AbstractDuring the second half of the nineteenth century, the occupation of shipmaster was transformed. It was remade as a profession ofandfor the middle class. This development followed from the specialization and division of labour in the shipping industry, and reflected the social divisions of an increasingly class-stratified society. The thesis advanced in this paper assigns a key role in this process to the dynamic of industrial capitalism. The paper argues that class-specific recruitment to the shipmaster's occupation put the values of the professional middle classes to the service of shipowners in the extension of their control over labour. The study examines several facets of this transformation: the state's contribution in the abandonment of mercantilist regulation of maritime labour and the introduction of masters' and mates' certificates of competency in the midnineteenth century; the role of the technological change from sail to steam on the nature and organization of the workforce; the owners' efforts to reduce the shipmaster to a wage employee whose self-interests and self-image made him distinctfrom other workers; and the structural changes in both the shipping industry and the systems of recruitment and training which ensured that the profession of shipmaster would gradually emerge as a middle-class preserve.The remaking of the profession of shipmaster illuminates the larger processes of social differentiation and cultural/ideological production associated with the division and specialization of labour in Victorian Britain. Examining this case in detail advances our understanding of class division in industrial society, particularly as it relates to the important, but singularly neglected, middle-managment professions.